The “Elephant in the Room”: Why and How Medium of Instruction and Decolonisation of Education are Linked - van Pinxteren, Bert (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2022)
The content of education and the medium in which it is delivered are generally seen as two different things: a curriculum that is in need of being “decolonised” can still be delivered in a colonial language. Likewise, a curriculum that is colonial in nature could in theory be delivered in any medium of instruction. This article argues that, seen from a macro perspective, this belief is incorrect. In African settings (and probably elsewhere as well), the medium of instruction and the content of that instruction are intricately linked. Evolution towards a decolonial educational system has to include a change in the medium of instruction if it is to be successful.